Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

Insights and Challenges of Co-Simulation-based Optimal Pulse Pattern Evaluation for Electric Drives - Hölsch, Lukas; Brosch, Anian; Steckel, Richard; Braun, Tristan; Wendel, Sebastian; Böcker, Joachim; Wallscheid, Oliver (IEEE Transactions on Energy Conversion)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Time-Optimal Model Predictive Control of Permanent Magnet Synchronous Motors Considering Current and Torque Constraints - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics